Role of polymetallic-nodule dependent fauna on carbon cycling in the eastern Clarion-Clipperton Fracture Zone (Pacific) - Stratmann, Tanja (Frontiers in Marine Science, 2023)
The abyssal seafloor in the Clarion-Clipperton Fracture Zone (CCZ) in the central Pacific is covered with large densities of polymetallic nodules, i.e., metal concretions containing iron, manganese, nickel, cobalt, and copper. Nodules are of economic importance for these metals, but they also host a variety of deep-sea fauna. In a recent study it was estimated that the removal of these nodules would lead to a loss of up to 18% of all taxa in the CCZ. Here, I assess the impact of removing these nodule-dependent taxa on carbon cycling at two sites (B4S03, B6S02) of the Belgian exploration license area in the eastern CCZ. For this purpose, I developed two highly resolved carbon-based food web models with 71 (B6S02) to 75 (B4S03) food-web compartments consisting of different detritus pools, bacteria, metazoan meiobenthos, macrobenthic isopods, polychaetes and other macrobenthos, megabenthic cnidarians, crustaceans, poriferans, holothurians and other invertebrate megabenthos, and fish. These compartments were connected with 303 (B6S02) to 336 (B4S03) links which were reduced by 5–9% when nodule-dependent faunal compartments were removed. The models estimated the “total system throughput” T.., i.e., the sum of all carbon flows in the food webs, in intact food webs as 1.18 mmol C m-2 d-1 and 1.20 mmol C m-2 d-1 at B4S03 and B6S02, respectively, whereby 69.8% (B6S02) to 71.2% (B4S03) of T.. flowed through the microbial loop. A removal of the nodule-dependent fauna did not affect this microbial loop but reduced the scavenger loop by 56.5% (B6S02) to 71.6% (B4S03). Overall, nodule-dependent fauna is responsible for only a small fraction of total carbon cycling at the eastern CCZ. Therefore, when the effect of prospective deep-seabed mining on carbon cycling is investigated, its impact on benthic prokaryotes and the microbial loop should be addressed specifically.